Policy as praxis: senior educators’ enactment of assessment policy reform - Hardy, Ian; Melville, Wayne (Power and Education, 2019)
This article reveals the multifaceted ways in which policy enactment was expressed as praxis in the context of assessment reform in Ontario, Canada. The research explores the way in which the Growing Success assessment policy was interpreted variously by different educators occupying senior roles within the district office in a single school district in northern Ontario. Drawing on neo-Aristotelian theorising, the research reveals how ‘policy in practice’ was expressed as a form of praxis, where such praxis is understood as morally committed and informed action oriented towards excellence in a field (in this case, education). While recognising the complexity of policy enactment, and how policy enactment can result in unforeseen and sometimes problematic outcomes, the research also reveals how policy enactment can have productive outcomes in relation to what are construed as the ‘internal goods’ of education. In the research presented, these productive outcomes included the capacity to facilitate teachers’ learning within and across elementary and secondary school sites; a critical, constructive focus on standardised measures of student learning in relation to academic outcomes; and the enhancement of student learning opportunities via cultural inclusion, particularly in relation to First Nations, Métis and Inuit students. In this way, the research validates a conception of policy as praxis and foregrounds how policy enactment can be understood in ways that promote the intrinsic integrity of educational practice, and the need to draw on these ‘internal goods’ in such enactment.